ANALISIS DAMPAK JUDI ONLINE SLOT PADA MASYARAKAT KOTA PERDAGANGAN SEBRANG DALAM PERSPEKTIF FIQIH MUAMALAH - Astrid Pane; Melisa (Jurnal At-Tabayyun, 2023)
With the development of technology, gambling has now moved to a slightly more elite venue. Technological advancements have changed the way gambling is played. Now gambling doesn't have to hide like it used to. Only by using a computer that has an internet connection can we play these prohibited games. The objectives of this study are: (1) Describe and analyze the online gambling community, (2) family reactions to internet gambling offenders; (3) the impact of online games on the decline of social values in society. The location of this research is Seberang trading city. This research used a phenomenological approach. The findings of this study indicate that online gambling undermines social values in the community of Kota Perdagangan Sebrang. One of them in this case includes a decrease in material values. If the perpetrator loses money through online gambling, they will run out of money. The key value is that if the perpetrator loses in online gambling, the perpetrator's action is to pledge his goods and do various ways to get money to do online gambling. Online gambling winnings also have a religious value that is used by the perpetrators to get drunk.